Modulation of lipid homeostasis in response to continuous or intermittent high-fat diet in pigs. (4th February 2015) - Puccinelli, E.; Gervasi, P. G.; Trivella, M. G.; Vornoli, A.; Viglione, F.; Pelosi, G.; Parodi, O.; Sampietro, T.; Puntoni, M.
Abstract : A high-fat diet is known to induce atherosclerosis in animal models. Dietary factors and timing of atherogenic food delivery may affect plasma lipoprotein content composition and its potential atherogenic effect. Increasingly often, humans spend periods/days eating in a completely unregulated way, ingesting excessive amounts of food rich in oils and fats, alternating with periods/days when food intake is more or less correct. We investigate the effect on lipid homeostasis of a high-fat diet administered either continuously or intermittently. We investigated control pigs receiving standard diet (C, n =7), pigs receiving a high-fat diet every day for 10 weeks (CHF, n =5), and pigs receiving a high-fat diet every other week for 10 weeks (IHF, n =7). IHF animals were shown to have a different lipid profile compared with CHF animals, with a significant increase in high-density lipoproteins (HDL) levels with respect to C and CHF groups. CHF also showed significantly higher values of TC/HDL cholesterol compared with C and IHF. Hepatic expression analysis of genes involved in lipid homeostasis showed an increasing trend of nuclear receptor LXRα along with its target genes in the CHF group and in the IHF group, whereas SREBP2 and LDLr were significantly inhibited. A significant correlation was found between ABCA1 expression and circulating levels of HDL-C. Periodic withdrawals of a high-fat atherogenic diet compared with a regular administration results in a different adaptive response of lipoprotein metabolism, which leads to a significantly higher plasma level of HDL-C and lower TC/HDL-C.